Estimation of Heating Device‘s Convective Heat Transfer of Heat Supply Systems with Rotational Heat Generator - A. P. Nesenchuk; I. L. Iokova; T. V. Rizova; P. G. Lasij; D. I. Shklovchik; Z. B. Aidarova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
In this article, on the base of heat exchange analysis in heat supply systems with rotational heat generator, a calculated formula for estimation of heat transfer from the surface of heating device is obtained, taking into account its probability (random) orientation in space. It is shown the most probable position of heating devices in heating system of mobile object.